2016
DOI: 10.1103/physreve.93.033006
|View full text |Cite
|
Sign up to set email alerts
|

Record-breaking events during the compressive failure of porous materials

Abstract: An accurate understanding of the interplay between random and deterministic processes in generating extreme events is of critical importance in many fields, from forecasting extreme meteorological events to the catastrophic failure of materials and in the Earth. Here we investigate the statistics of record-breaking events in the time series of crackling noise generated by local rupture events during the compressive failure of porous materials. The events are generated by computer simulations of the uniaxial co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The model proved to be very successful in reproducing the observed power law statistics of burst sizes, energies, durations, and of the waiting times between consecutive events [18,19]. Most recently we have also analyzed the details of the time series of bursts of the model searching for the record breaking events [20].…”
Section: Simulation Of Uniaxial Compressionmentioning
confidence: 98%
See 1 more Smart Citation
“…The model proved to be very successful in reproducing the observed power law statistics of burst sizes, energies, durations, and of the waiting times between consecutive events [18,19]. Most recently we have also analyzed the details of the time series of bursts of the model searching for the record breaking events [20].…”
Section: Simulation Of Uniaxial Compressionmentioning
confidence: 98%
“…The fault itself develops as a localized shear band formed by multiple fracturing and refracturing both prior to and during slip. To study this problem, recently we have introduced a discrete element model of porous sedimentary rocks which captures the essential ingredients of the materials' microstructure and of the dynamics of breaking [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The record statistics (RS) of stochastic time series has attracted a great attention due to its relevance for weather, climate and earthquake research [50][51][52][53][54][55] . The RS analysis has proven very successful to reveal trends, correlations, and spatio-temporal clustering of events in complex evolving systems [50][51][52][53][54][55][56][57][58][59] . For fracture processes, here we demonstrate that the waiting time between consecutive record breakings, i.e.…”
Section: Record Statistics Of Bursts Signals the Onset Of Acceleratiomentioning
confidence: 99%
“…In our previous studies, the model was used to investigate the uniaxial compression of cylindrical samples focusing on both the time evolution of the fracture process [14,15,20] and on the spatial structure of the emerging damage [21]. We demonstrated that the gradual cracking proceeds in bursts of beam breakings, analogous to sources of acoustic emissions or crackling noise of real experiments.…”
Section: Discrete Element Simulation Of Compressive Failurementioning
confidence: 99%